Falls prevention resource for the aboriginal population in Western Australia. (7th October 2012) - Anderson, E; Harwood, S; Page, T; Butler, S
Abstract : Background: This project relates to falls prevention amongst Aboriginal communities. Although not necessarily a priority area in the eyes of health professionals, a number of chronic health conditions faced by this population contribute to their risk of falling. Aim: To establish population specific and culturally appropriate resources to provide a consistent and coordinated approach to informing the Aboriginal population in Western Australia of the contributing risk factors and strategies to assist in the prevention of falls. Methods: A needs assessment and stakeholder consultation was conducted with Aboriginal Health Workers from the Kimberley and South West regions of WA. Working parties and reference groups were established and consulted to guide the development of the resources format, content and method of dissemination as well as to ensure the resources were based on evidence and best practice guidelines. Outcome: A 'Falls Prevention for Aboriginal People: Toolkit for Health Professionals and Aboriginal Health Workers' was finalised. Continuous improvement occurred with assistance from the South West Aboriginal Medical Service. From this trial an easy to use action plan has been developed as well as a culturally appropriate adaptation of an 'Up From The Floor' poster. The resource is currently going through an evaluation to further improve the resource for a new print run due in early 2013. Contribution to the Field: There are limited resources to promote the prevention of falls targeting the Aboriginal community in Australia. This resource has been popular not only in Western Australia but has received interest from other states.